Mevlevilik, Mevlana ve Şeyh Galip Üzerine İncelemeler / Studies on Mawlawiyah, Mawlana and Sheikh Ghalib - Kacar, Mucahit; Arslan, Omer; Karakus, Yasemin (Istanbul University Press, 2022)
Mawlawiyah, which has a history of nearly eight centuries, was institutionalised as a sufi school and has had widespread effects, in addition to pioneering the formation of one of the most influential sources in Turkish culture, art, and literature. When compared to other sufi schools, the most striking feature of Mawlawiyah is that it allocates a central place to art and literature within its institutional culture. Therefore, from the thirteenth century to the present day, the number of poets who were followers of the Mawlawiyah or Mawlawi culture in Turkish literature is more than three hundred. In addition to historical figures such as Sheikh Ghalib, who are directly identified with Mawlawiyah, the reflections of this cultural accumulation also appear in the writing experiences of authors who are not directly affiliated with Mawlawi culture, such as Halide Edib Adıvar and Ahmet Hamdi Tanpınar, due to their interest in the culture. In recent years, parallel to the increasing interest in Mawlana, Mawlawiyah, and Sheikh Ghalib around the world as the culture industry put mysticism on its agenda , new dimensions have been added to the subject. Some of the studies in this book, which are composed within the framework of these new dimensions, focus on the classical period and Mawlana's personality, works, life, new research on Mawlawiyah, and well-known written sources on these issues. In the studies dealing with the modern period, the images of Mawlana and Mawlawiyah are analysed in different fields, from poetry to novels and socioeconomic dimensions of mysticism today. In this context, Mevlüt İlhan and Ermiş Dandan, in their article titled "Osman Fevzi Olcay's Muhtasar Menâkıb-ı Mevlânâ", present information about Muhtasar Menâkıb-ı Mevlânâ of Osman Fevzi Olcay, who has produced many historical works, and then include the text of his work. Özlem Düzlü, in "Mawlawis in Keçecizâde Izzet Molla's Writings", evaluates a stanza that was devoted to the members of the Mawlawiyah by Izzet Molla, who has added a couplet about Mawlana or Mawlawiyah at the end of almost every ghazal in his diwan called Bahâr-ı Efkâr and wrote many poems about Mawlana, Mawlawi elders, and Mawlawiyah. Pointing out that in the poem, which consists of eighteen couplets with the redif "Mawlawi", the positive characteristics of the Mawlawis are generally mentioned, Düzlü also observes that İzzet Molla further emphasises the existence of people who could be the target of criticism from within or outside the sect due to their negative behaviours. Focusing on the history of literature in their article "Dr. Rıza Nur's Studies on Jalâl al-Dîn Muhammed Rûmî, Sultan Veled, and Sheikh Ghalib's Poems", Yasemin Karakuş and Ömer Arslan draw attention to the revealing of Rıza Nur's Evolution of Turkish Poetry History and Its Analytical Study, which has not been known until today, within the framework of the content of Nur's work, then discuss how Mawlana, Sultan Veled, and Sheikh Ghalib's poems and literary personalities were examined by Dr. Rıza Nur. In one of the two studies dealing with Mawlawiyah and Mawlana in modern Turkish poetry, Ahmet Murat Özel finds that a strong representation does not occur in modern literature, despite the founding role of Mawlana and Mawlawiyah in classical literature. Özel, who attributes this to the lack of attention paid to tradition by modern poets, evaluates the representation of Mawlana and Mawlawiyah in modern Turkish poetry as an "emotional fidelity but a poetic farewell". Sevim Güldürmez, on the other hand, concentrates on the works of many different authors in her article, which deals with the various forms of appearance of Mawlana in modern Turkish poetry. Güldürmez, claiming that each poet constructs their own Mawlana image, analyses the existence of Mawlana in modern Turkish poetry from a different framework apart from the fact of establishing a relationship with tradition. In parallel with Güldürmez, Derya Güllük also examines the variations in the aspects of Mawlana and Mawlawiyah in Turkish novels. According to Güllük's article, the representation of Mawlana as a historical figure and the Mawlawi culture created by his followers over the centuries in Turkish novels differs in line with the personal selectivity of the novelists and their issues, and fiction writers construct their own Mawlana image. Muhammet Salman and Resul Kırmızıdemir focus on İhsan Oktay Anar's novel Suskunlar. Salman and Kırmızıdemir offer an alternative reading suggestion for this novel through the way Mawlawiyah is perceived within the journey of the novel character Eflâtun representing mystical self-fulfilment, by a deconstructive approach to the understanding of the truth is distorted in a postmodern situation; however, they point out that this deconstruction has also the potential to help reach the truth, not nihilism. The position of Mawlawi whirling ceremonies, one of the first symbols that come to mind when Mawlawiyah is mentioned in today's socioeconomic practices of mysticism, is among the issues discussed in the book. Seda Aksüt points out the danger posed to the whirling ceremonies by decontextualization, which is one of the risk factors that threatens the authenticity of this cultural heritage, and makes suggestions for building an effective awareness of conservation.